Studi potensi lanskap wisata Kampung Rawa Gede, Desa Tugu Utara, Kabupaten Bogor, berbasis partisipatif - Khrisrachmansyah, Rezky; Rafael, Risco Noverio (Jurnal Arsitektur Lansekap; Vol.7, No.1, April 2021DO - 10.24843/JAL.2021.v07.i01.p13, 2021)
Rawa Gede Hamlet is located in Tugu Utara Village, Bogor Regency, and nearby Mount Gede Pangrango. Beautiful sceneries of tea plantations and horticulture fields exist with various natural features such as waterfall and spring lake. However, a community business which manage coffee plantation awarded as the best national coffee called Cibulao Coffee also existed and give economical value to the local people. Therefore, Rawa Gede Hamlet has a potential to be developed as a tourism destination. The aim of this sudy is to assess how potentials Rawa Gede Hamlet as a tourism hamlet including both spatial and nonspatial aspects. In addition, the process of the study was a combination of qualitative and quantitative methods by using suitability scoring, community mapping, interview, and focus group discussion. This study also drove participatory approach as a core of research for design. The result showed that there are several tourism destination that had higher points than other according to tourism suitability. Those objects were Telaga Saat, Bukit Gerindra, Wisata Alam Gunung Luhur, Wisata Alam Gunung Kencana, dan Curug Sawer. Furthermore, this study was emerged also with non-spatial aspects and those acted as an identity of Rawa Gede Hamlet.